Traveling Salesman Problem with Time Specific Profit on Resource (The Journal of Academic Development, 2023)
In general, the classical Traveling Salesman Problem (TSP) with assumptions of uniform travel times does not fully apply due to factors like fluctuating traffic conditions, diverse transportation modes, and varying resource availability. This research seeks to tackle the optimization of time-specific profit within the TSP framework while considering travel times dependent on available resources. The study also introduces an approach to extend the classical TSP model, accommodating resource-dependent travel times to maximize profit from visiting a specific set of locations within a defined timeframe. A mathematical formulation is presented, integrating the variables of time travel variability, resource availability and profit generation into the TSP framework. This method acknowledges the dynamic nature of travel times and efficiently utilizes resources to achieve optimal profit. Furthermore, it is ensured that identifying the optimal solution using this approach will not pose a greater computational challenge than solving the classical TSP.